Blueberry consumption challenges hepatic mitochondrial bioenergetics and elicits transcriptomics reprogramming in healthy wistar rats - Nunes, Sara (2020)
An emergent trend of blueberries’ (BB) “prophylactic” consumption, due to their phytochemicals’ richness and well-known health-promoting claims, is widely scaled-up. However, the benefits arising from BB indiscriminate intake remains puzzling based on incongruent preclinical and human data. To provide a more in-depth elucidation and support towards a healthier and safer consumption, we conducted a translation-minded experimental study in healthy Wistar rats that consumed BB in a juice form (25 g/kg body weight (BW)/day; 14 weeks’ protocol). Particular attention was paid to the physiological adaptations succeeding in the gut and liver tissues regarding the acknowledged BB-induced metabolic benefits. Systemically, BB boosted serum antioxidant activity and repressed the circulating levels of 3-hydroxybutyrate (3-HB) ketone bodies and 3-HB/acetoacetate ratio. Moreover, BB elicited increased fecal succinic acid levels without major changes on gut microbiota (GM) composition and gut ultra-structural organization. Remarkably, an accentuated hepatic mitochondrial bioenergetic challenge, ensuing metabolic transcriptomic reprogramming along with a concerted anti-inflammatory pre-conditioning, was clearly detected upon long-term consumption of BB phytochemicals. Altogether, the results disclosed herein portray a quiescent mitochondrial-related metabolomics and hint for a unified adaptive response to this nutritional challenge. The beneficial or noxious consequences arising from this dietary trend should be carefully interpreted and necessarily claims future research.